Combination of strategies to initiate clozapine for refractory schizophrenia in a patient with low neutrophil levels. Issue 10 (13th October 2022) - Takanobu, Keisuke; Hashimoto, Naoki; Ishikawa, Shuhei; Kusumi, Ichiro
Abstract : Clozapine is the only drug with confirmed efficacy for refractory schizophrenia; however, its use is restricted due to the risk of potentially life-threatening side effects, such as agranulocytosis. Although this restriction ensures safety against haematological risks, some patients with refractory schizophrenia who have low neutrophil levels may miss the opportunity to receive clozapine treatment. We herein report the case of a patient with refractory schizophrenia and low neutrophil levels who was successfully initiated on clozapine treatment after the use of several methods for increasing neutrophil levels. These strategies consisted of discontinuation of antipsychotics, treatment with lithium carbonate and adenine, and light exercise before blood testing. Combining these procedures may be an effective option in the treatment of patients with refractory schizophrenia whose neutrophil levels are not sufficient to initiate clozapine.